Bifurcation stenting: If the shoe doesn't fit. Issue 1 (19th January 2023) - Chaus, Adib; Uretsky, Barry F.
Key Points: The modified TAP procedure (m‐TAP) utilizes indenting a MV non‐compliant balloon with the side branch stent to minimize stent struts in the main vessel. This novel technique results in larger stent area and a shorter neocarina than traditional TAP. With the general increase in use of IVUS to improve long‐term outcomes, m‐TAP looks to be a welcome improvement in the TAP approach.